The Association Between the CALLY Index and All-Cause Mortality in Patients with COPD: Results from the Cohort Study of NHANES 2007–2010 - Ding Y; Liu Y; Yu J; Cai C; Fu L; Zhu J; Yang S; Jiang Y; Wang J (International Journal of COPD)
Yu Ding,1 Yuxia Liu,2 Jianjian Yu,2 Chengsen Cai,2 Lina Fu,2 Jie Zhu,3 Shengzhen Yang,4 Yu Jiang,1 Jun Wang2 1The First Clinical Medical College, Shandong University of Traditional Chinese Medicine, Jinan, People’s Republic of China; 2Department of Pulmonary and Critical Care Medicine, The Second Affiliated Hospital of Shandong University of Traditional Chinese Medicine, Jinan, People’s Republic of China; 3Department of Pharmacy, The Second Affiliated Hospital of Shandong University of Traditional Chinese Medicine, Jinan, People’s Republic of China; 4Department of Pulmonary, Rizhao Hospital of Traditional Chinese Medicine, Rizhao, People’s Republic of ChinaCorrespondence: Jun Wang, Department of Pulmonary and Critical Care Medicine, The Second Affiliated Hospital of Shandong University of Traditional Chinese Medicine, Jinan, People’s Republic of China, Email jnwj660606@163.comPurpose: The C-reactive protein (CRP)–albumin–lymphocyte (CALLY) index is a newly developed biomarker that combines measurements of CRP, serum albumin, and lymphocyte count. This index provides a thorough assessment of a patient’s inflammation level, nutritional condition, and immunological function. The objective of this study is to examine the correlation between the CALLY index and all-cause mortality in COPD patients.Methods: We calculated the CALLY index using data from the National Health and Nutrition Examination Survey (NHANES) for the 2007– 2008 and 2009– 2010 cycles, extracted from the participants’ peripheral blood samples. The study utilized Kaplan-Meier curves, restricted cubic spline (RCS) curves, and Cox regression analysis to evaluate the relationship between the CALLY index and the risk of all-cause mortality in COPD patients. To assess the predictive accuracy of the CALLY index, we calculated the area under the receiver operating characteristic (ROC) curve (AUC).Results: The study included 1,048 participants and found a significant negative correlation between the CALLY index and all-cause mortality in patients with COPD. The CALLY index was a major predictor of survival in COPD patients [fully adjusted model: in the 3rd quartile, HR = 1.61, 95% CI: 1.02– 2.52, p = 0.039; in the 2nd quartile, HR = 2.11, 95% CI: 1.22– 3.65, p = 0.008; in the 1st quartile, HR = 3.12, 95% CI: 2.00– 4.85, p < 0.001]. The RCS curves demonstrated a non-linear association between the CALLY index and all-cause mortality in COPD patients. The areas under the curve (AUC) in predicting 5- and 10-year all-cause mortality were 0.693 and 0.656.Conclusion: The CALLY index has a strong relationship with all-cause mortality in patients with COPD in the US and could serve as a prognostic biomarker for these patients.Keywords: chronic obstructive pulmonary disease, the C-reactive protein–albumin–lymphocyte index, national health and nutrition examination survey, biomarker